The Efficacy of the Void in Ancient Atomism - Rodríguez Arriagada, Marcelo (Byzantion Nea Hellás, 2023)
The philosophical position of the atomists is a strategy adjusted to the aleatory points of the compound that is each thing, be it a world, an animal, a dream, a State, etc. From this point of view, in this writing we will maintain that the void (kenón) is not the foundation of the movement of the atoms, but the “free field” that makes possible the conjunction or meeting of the elements, that is, the contingent beginning of a transformation with no anticipated or foreseeable end.